Монгол, манж албан бичгийн харьцаа - М.Баярсайхан (Acta Mongolica, 2007)
As accepted, the Manchurian literature has taken its origin from the official writings in the Mongolian language and script The earliest inherited monument of the written Manchurian is a collection of important state-running papers and documents under the name "Ejehe dangse iu Man Tang/. An observing of the items in this collection clearly shows that the procedure and style of the Mongolian official papers in the period of the Northern Yuan Dynasty are copied in them almost wholly. Regarding the Manchurian official paperwork it can be traced that since the crigin during the Later Jin Dynasty it had been following the traditions of the Mongolian official paperwork till up-to the Qing period when the procedures of the state-running paperwork were over reviewed in r of times by the Khans’ oeders in accordance with the traditional Chinese style and established word expressings. Conceming the Mongolian official paperwork the author asserts that since the earlier times it had a relationship to the Chinese tradition and in spite of some changes during the periods of the Mongollan states and the Northem Yuan Dynasty, as well as in the Qing period it remained the same in its basic form and structure. The Mongolian and Manchurian official papers in the Qing period coincide in their form and structure and developed in parallel.